2021
DOI: 10.1016/j.prnil.2020.11.002
|View full text |Cite
|
Sign up to set email alerts
|

RNA-seq profile of African American men with a clinically localized prostate cancer

Abstract: Background Prostate cancer in African American (AA) men has a poor prognosis. This study aimed to identify potential genetic risk factors for prostate cancer in AA men. Methods We used prostate cancer tissue from 61 patients who underwent radical prostatectomy. We compared somatic gene expression in Caucasian (CA) and AA men using RNA sequencing. Results By comparing the RNA-seq data obtained from prostate cancer tissue between AA and CA men,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 25 publications
(23 reference statements)
0
11
0
Order By: Relevance
“…Characterizing the genes and pathways linked to AA prostate tumor samples will allow researchers to better understand differences in tumor progression and treatment response between subgroups. When we searched studies that generated RNAsequencing or microarray data from prostate tissue samples, and directly compared gene expression profiles between AA and EA prostate cancer patients, we found eight different studies (25)(26)(27)(28)(29)(30)(31)(32) (Table 3).…”
Section: Genes Differentially Expressed Between Aa and Ea Prostate Ca...mentioning
confidence: 99%
See 1 more Smart Citation
“…Characterizing the genes and pathways linked to AA prostate tumor samples will allow researchers to better understand differences in tumor progression and treatment response between subgroups. When we searched studies that generated RNAsequencing or microarray data from prostate tissue samples, and directly compared gene expression profiles between AA and EA prostate cancer patients, we found eight different studies (25)(26)(27)(28)(29)(30)(31)(32) (Table 3).…”
Section: Genes Differentially Expressed Between Aa and Ea Prostate Ca...mentioning
confidence: 99%
“…These genes were also reported to be upregulated in TCGA prostate cancer AA patients. CRYBB2 specifically was found by two studies to be overexpressed in AA men (28,30) while another study indicated that it was underexpressed in AA men relative to EA men prostate tissue samples (29). Rayford et al also reported that the biological pathways upregulated in AA patients were related to inflammatory response (e.g.…”
Section: Genes Differentially Expressed Between Aa and Ea Prostate Ca...mentioning
confidence: 99%
“…However, it does not accurately represent the molecular state of the tumor cells or their biological characteristics. 1 , 2 , 3 , 4 , 5 Serum PSA is often measured as high in men without PCa or low in advanced PCa. Many other biological markers have been studied to compensate for this and PSA mRNA has been proposed as a novel marker.…”
Section: Discussionmentioning
confidence: 99%
“…However, it does not accurately evaluate the biological characteristics of prostate cancer cells, and there is a need to develop better biological markers to assess the progression of prostate cancer. 1 , 2 , 3 , 4 , 5 In particular, as the treatment for metastatic PCa is diversified, there is increased interest in the development of biomarkers to predict treatment responsiveness.…”
Section: Introductionmentioning
confidence: 99%
“… 1 Although the majority of patients with locally advanced and metastatic disease initially respond to androgen deprivation therapy (ADT), most will progress into metastatic castration-resistant PCa (mCRPC). 2 However, some unique RNA-seq profiles of Pca had been detected, 3 and the instability of RNA limits its application in clinical testing. There had been some previous studies suggesting homology recombination repair (HRR) was the most important pathway to repair DNA double-strand break, which was one of the most genotoxic forms of DNA damage and tumori-genesis.…”
Section: Introductionmentioning
confidence: 99%